(untitled) (Linguistics in Amsterdam, 2011)
Sri Lanka Malay is a very transparent language. The domains which can be considered non-transparent are limited to apposition, repetition of elements, two portmanteaus, and right extraposition of heavy elements. Sri Lanka Malay does not show any of the more salient cases of opacity, such as gender, agreement, conjugation, declension, grammatical relations, or expletives.